Pengaruh Subjective Well-Being Terhadap Kinerja Karyawan Di PT. X Di Jakarta - Adeline, Aurelia; Basaria, Debora; Fahlevi, Reza (Psikologi Prima, 2024)
This study explores subjective well-being's influence on employee performance at PT X, a company in the building chemical industry sector in Jakarta. This research is based on the importance of employee well-being in achieving optimal performance and how subjective well-being can be a determining factor, as supported by several studies that show a positive influence between subjective well-being and performance. Initial observations showed high employee performance results, with most employees able to complete work quickly and precisely, as well as a work atmosphere full of happiness and positive emotions based on the results of an initial survey of 30 employees. This study used a quantitative approach with data collected through an online questionnaire distributed to 165 employees of PT X. The instruments used included the Satisfaction With Life Scale (SWLS) and Scale of Positive and Negative Experience (SPANE) to measure subjective well-being, as well as the Individual Work Performance Questionnaire (IWPQ) to measure employee performance. Using a simple regression test, the analysis results obtained an R square value of 9.7% and a significance level of p < 0.05, indicating that subjective well-being significantly affects the employee performance of PT X in Jakarta.